Kompos Tandan Kosong Kelapa Sawit, Hubungannya dengan Karakter Tanah dan Hasil Tanaman Terong Ungu - Abdillah, Muhammad Helmy; Handika, Lidwina Reni; Iswahyudi, Herry; Lukmana, Mila; Rahmawati, Linda; Indriani, Indriani; Widiyastuti, Dewi Amelia (Jurnal Pertanian, 2024)
Crude palm oil (CPO) production continues to be accelerated every year to meet domestic needs and large export demands from China, India, Pakistan, Bangladesh, Japan, and countries in the Middle East region. Indonesia, as the largest CPO producer in the world, is taking on this role to increase the country's competitiveness by continuing to meet CPO demand and needs. However, the high level of CPO processing impacts increasing by-products from palm oil factories. Empty bunches fruit from Palm oil (EFB) are the most common by-product of CPO production. This is a big problem because accumulation will be the main source of environmental damage and pest explosions. Processing EFB into soil conditioners can be an initiative to reduce the accumulation of EFB in factories. However, its effect is not yet known with certainty on several plants cultivated on marginal dry land, such as Ultisol soil. Research aimed to analyze the relationship between the application of various EFB composts to bulk density, percentage of water content, degree of soil acidity, increase in number of leaves, number of eggplants, and weight of eggplant. The research results showed that EFB in the form of compost applied could influence the bulk density, percentage of water content, degree of soil acidity, increase in the number of leaves, and weight of eggplant, but did not affect the number of eggplant. Application EFB positively correlated with the percentage of water content, degree of soil acidity, increase in number of leaves, and weight of eggplant, with determination effects. At the same time, EFB compost had a negative correlation with bulk density.